MEMBIDIK PEMBACA GENERASI MUDA (Studi Kasus Strategi Komunikasi Pemasaran Terpadu Harian Kompas dalam Membidik Pasar Pembaca Anak Muda) - , CHINTYA BAMBY; , Rahayu, S.IP., M.Si., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Conrad C. Fink stated in his 1996âs book Strategic Newspaper Management that newspaper readership will die, unless newspaper companies start attracting enough young readers. Fink believed that there must be a constant renewal of readers among young people. Finkâs statement was supported by Rupert M. Murdoch, also known as The Last Media Mogul, back in 2004 when he was giving a speech in front of the American Society of Newspaper Editors. Murdoch predicted that âdigitalâ will be the future, as in the future of media. And apparently, heâs right, because nowadays people can get their daily dose of news and informations from their smartphone, tablet, and even their MP3 player without having to worry about time and place. It is a challenge for the newspaper industry to embrace that digital exodus, instead of denying its power, especially concerning the young readers. The aims of this thesis are to find out what kind of strategic marketing communication that a big newspaper company (Harian Kompas) applies to attract its young readers, from the basic planning to the choosing which strategic marketing communication elements that can accommodate the target market profile, until the exact implementation of those strategic marketing communication elements and finally the evaluation that Harian Kompas does for each strategic marketing communication elements. Research finds Harian Kompas uses six strategic marketing communication elements, which are advertising, Corporate Social Responsibility (CSR), event and experiences, sales promotion, interactive/internet marketing, and Word of Mouth (WoM). Research also finds that MuDA, Harian Kompasâ weekly spread for young readers of 15-18 age, is indeed embracing the digital in order to keep up with its young readers dynamic and MuDA also differentiates itself from its competitors by creating a community in nine big cities in Indonesia, organizing annual events and competitions, and giving opportunities to the young people to write on the weekly spread because Harian Kompas believes that young people understand their peers better, therefore its âDari, Oleh, dan Untuk Anak Mudaâ motto.